Single women's happiness in terms of social support and religiosity - Islahiani Rufaidah; Setiasih Setiasih (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2024)
In Indonesia, single women continue to face negative stigma. They are often perceived as